2021
DOI: 10.1093/pubmed/fdab220
|View full text |Cite
|
Sign up to set email alerts
|

How effective are digital interventions in increasing flu vaccination among pregnant women? A systematic review and meta-analysis

Abstract: Background Flu can have serious consequences for pregnant woman and unborn babies. Vaccination provides safe and effective protection, yet uptake among pregnant women is below national targets. Digital interventions are effective at increasing adherence to health interventions. Aims This review aimed to establish whether digital interventions are effective at increasing rates of flu vaccination among pregnant women, and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The eight studies that assessed publication bias did so using funnel plots [ 40 , 65 , 67 , 70 , 72 , 74 ], Egger’s [ 65 , 67 , 70 , 73 , 80 ] or Begg’s tests [ 70 , 80 ]. Although several predictors did not acquire enough included studies to assess publication bias [ 40 , 65 , 74 ], reviews mostly concluded that there was no publication bias [ 65 , 70 , 73 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eight studies that assessed publication bias did so using funnel plots [ 40 , 65 , 67 , 70 , 72 , 74 ], Egger’s [ 65 , 67 , 70 , 73 , 80 ] or Begg’s tests [ 70 , 80 ]. Although several predictors did not acquire enough included studies to assess publication bias [ 40 , 65 , 74 ], reviews mostly concluded that there was no publication bias [ 65 , 70 , 73 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 19 included reviews ( Table 2 ) can be divided into three main categories; nine assessed barriers and facilitators to COVID-19 [ 67 , 69 71 , 73 , 77 80 ], four assessed barriers and facilitators to one or both of Influenza and Pertussis [ 38 , 40 , 64 , 65 ], and six assessed the effectiveness of interventions to increase vaccination of one or both of Influenza and Pertussis [ 66 , 68 , 72 , 74 76 ]. Of those in the latter two categories, six studied Influenza alone [ 64 , 65 , 72 , 74 76 ], one studied Pertussis only [ 68 ], and three included both [ 38 , 40 , 66 ]. No reviews assessed the effects of interventions to increase COVID-19 vaccination, likely due to the short period from the start of the COVID-19 outbreak.…”
Section: Resultsmentioning
confidence: 99%
“…A more nuanced programme, seeking to build relationships between providers and communities over time, and targeted social media messaging is worth considering for younger and older women, and those of Black and Black British ethnicity. 47 49 …”
Section: Discussionmentioning
confidence: 99%
“…A more nuanced programme, seeking to build relationships between providers and communities over time, and targeted social media messaging is worth considering for younger and older women, and those of Black and Black-British ethnicity. [47][48][49] Women with pre-existing medical conditions are an important group to target because of the additional morbidity and mortality risks associated, and GP information systems are likely to capture this accurately as part of their disease registers, especially if financially incentivised. 50 There may well be questions to address on who is best placed for discussing immunisation with women, especially since they will often be seen by both primary care and antenatal care teams.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Regarding text messaging platforms, there were too few studies in our review to draw a conclusion regarding their effectiveness as digital platforms for alcohol abstinence. Previous studies on the use of text messaging services to raise awareness about smoking cessation and flu vaccinations among pregnant women have shown mixed results, with some studies reporting promise compared to nontailored or internet platforms [ 35 , 36 ], and others claiming that they are less effective than visually engaging interventions like videos and iBooks [ 35 ]. It should be noted that in the 2 text messaging trials in our review, the entire evaluation period only lasted for 4 weeks, which was relatively shorter than the period of the other platforms [ 37 ].…”
Section: Discussionmentioning
confidence: 99%